MELIHAT SISA-SISA KEJAYAAN MAJAPAHIT DI PUSAT INFORMASI MAJAPAHIT SEBAGAI UPAYA PENGUAT JATI DIRI BANGSA - Zuraidah Zuraidah (Journal Social and Humaniora, 2017)
Majapahit was a great kingdom, at Clasic Era wich has thousands of tangible adn intangible cultural heritage. Various archaeological ancient at majapahit Era very atractive and challenging the scientist to examine and investigate the based on their aspect and knowlegde. The article examined the remain of Majapahit fame at Majapahit Information Centre, wich purpose of Indonesian identity reinforming. The National Reinforming is very important to present global cultural influences it also stimulated awareness and a?ection concerning about the importan of archaeological ancient Keywords: Majapahit Information Center, Ancient, Identity